Unaspis lansivora sp. n. (Hemiptera: Diaspididae), a new pest of Lansium domesticum (Meliaceae), and a key to Unaspis species - Watson, Gillian W. (Zootaxa, 2015)
Since 2004, an undescribed species of Unaspis (Hemiptera: Diaspididae) has become a damaging pest on Lansium domesticum Corrêa in the Philippines. Its attack on the leaves causes premature senescence and defoliation, resulting in the production of few, underdeveloped, sour fruit and sometimes killing the trees. The scale was misidentified initially as Lepidosaphes ulmi (Linnaeus) and then as Unaspis citri (Comstock), but further study indicated that it was an undescribed species of potential plant quarantine significance. The pest is described as U. lansivora sp. n. and an identification key to all 19 species of Unaspis is provided. Its distribution, host range and prospects for its biological control are discussed.